96 Meta-analysis of placebo-controlled trials of Levosimendan in acute myocardial infarction. (8th December 2021) - Tumminello, Gabriele; Cereda, Alberto; Barbieri, Lucia; Biondi-zoccai, Giuseppe; Lucreziotti, Stefano; Mafrici, Antonio; Carugo, Stefano
Abstract: : The treatment of acute myocardial infarction is the early revascularization strategy. Heart failure and cardiogenic shock may complicate acute myocardial infarction nevertheless the best disposable strategy applied. Levosimendan is relatively new drug to treat heart failure with a peculiar mechanism of action: calcium sensitization of myocardial fibres. Levosimendan has a direct inotropic effect but also pleiotropic effects; through the K+ATP channels opening it has also a vasodilator effect with may participate concretely to the global effects of the drug. Literature has focused the attention on the anti-heart failure and anti-cardiogenic shock properties of Levosimendan, but it may have effects also preventing the development of myocardial insufficiency in the acute setting of acute myocardial infarction. Scope of the meta-analysis is to evaluate the effect of Levosimendan on acute myocardial infarction in placebo-controlled trials. : Based on the eight studies selected we found a beneficial effect of Levosimendan on acute and long-term mortality of patients affected by acute myocardial infarction with no significative increase in adverse events (Figure 1). With caution in interpreting the results of this meta-analysis, our data support the idea that Levosimendan may already have a role in the treatment of acute ischaemic heart disease. Further studies, specifically designed to investigate the early role in the treatment of ischaemic heart failure, are needed.